8. EVALUATION OF TREATMENT OUTCOMES FOR TIBIAL PLATEAU FRACTURES WITH THREE-COLUMN INJURY AT CAN THO CENTRAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Tibial plateau fractures can result from high-energy mechanisms such as traffic accidents in young individuals or low-energy trauma, such as falls in the elderly. Classification of tibial plateau fractures not only helps estimate the severity of the injury but also guides treatment planning and predicts the prognosis after bone fixation. Although several classification systems exist for tibial plateau fractures, the Schatzker classification remains widely used. With the advent of computed tomography (CT), more comprehensive classifications have been developed, facilitating a deeper understanding of tibial plateau fractures. In 2010, Luo and colleagues proposed the three-column concept (medial, lateral, and posterior columns). This classification system is now widely applied in many countries worldwide.Objective: To evaluate the treatment outcomes of tibial plateau fractures with three-column injury using internal fixation.Subjects and Methods: A cross-sectional descriptive study was conducted on 21 patients with closed tibial plateau fractures involving all three columns, confirmed by CT scan images at Can Tho Central General Hospital from 2022 to 2024.Results: The average age of patients was 46.1 years, with 14 males and 7 females. The most common associated injury was a fracture of the proximal fibula (47.62%), followed by medial collateral ligament injury (14.8%). The majority of surgeries were performed within 7 days after injury (47.62%). Bone grafting was required in 5 cases. The most commonly used surgical approach was the "extended or modified anterolateral + posteromedial" approach, accounting for 61.9%. There was one case of superficial wound infection and two cases of medial instability. The average time to bone union was 14.6 weeks. Functional recovery at 6 months, as assessed by the Rasmussen score, showed good to excellent outcomes in 19 patients (90.48%) and moderate outcomes in 2 patients (9.52%).Conclusion: The three-column concept is a useful classification system for clinical diagnosis, surgical planning, fracture fixation, and prognosis evaluation of complex tibial plateau fractures.
Keywords: tibial plateau fracture; three-column concept; internal fixation